Technologie informacyjno-komunikacyjne a zarządzanie sieciami partnerskimi - Butryn, Beata (Information-communicative technologies versus partnership nets management, 2006)
The article shows lhal information-communicative technologies have decisive influence on management. Their dynamic development makes the extension of process management of an organization to partnership nets management necessary. This management includes three areas: processes of a particular organization, processes connected with relations with clients as well as joint processes with partners. The management of partnership nets is based on net platforms.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1132, s. 70-77